P05.46 Metachronous malignancies and brain tumor in children with germline TP53 mutation. (19th September 2018) - Guidi, M; Giunti, L; Buccoliero, A; Farina, S; Fonte, C; Caporalini, C; Moscheo, C; Censullo, M; Genitori, L; Sardi, I
Abstract: Background: Somatic TP53 mutations have been reported to occur in almost every type of cancer. They are common alterations in brain tumors. Nevertheless, germline mutations of TP53 gene are linked to Li-Fraumeni syndrome (LFS), a tumor susceptibility condition, characterized by an increased risk of developing early synchronous or metachronous malignancies. TP53 germline mutations have also been reported in individuals with no family history or with a family history not fulfilling LFS characteristics. Material and Methods: We retrospectively considered 7 patients with brain tumors followed at the Neuro-Oncology Unit between September 2008 and January 2018. The median age at diagnosis was 13, 7 years (range 1–31); Six patients were male and one female. Five patients developed metachronous tumors. Two LFS patients had only a primary anaplastic astrocytoma. Five (71, 4%) patients had primary brain tumor (3 anaplastic astrocytoma, 1 ependymoma, 1 medulloepithelioma). Molecular analysis of TP53 gene was performed in all patients. Family's cancer history was investigated. Results: Six patients (85, 7%) had a germline TP53 mutation all contained between exons 4 and 7. Only one patient with metachronous tumors (leukemia and ependymoma) and without a family's cancer history did not show a TP53 mutation. Two patients (28, 6%) were negative for family's cancer history but positive for germline TP53 mutation, ones with history of primary medulloepithelioma and osteosarcoma. The second patient had two brain tumors (anaplastic astrocytoma and PNET). The second tumors developed after two years from the first diagnosis. One LFS patient positive for germline TP53 mutation died for an anaplastic astrocytoma. The other four patients (57, 1%) resulted positive both for germline TP53 mutation and for family's cancer history. The median time between the first and second diagnosis was 7, 2 years. Conclusion: Germline TP53 mutation predisposes to develop synchronous or methachronous tumors even after many years. Our study evidenced that germline TP53 mutation is also frequent in brain tumor patients without cancer family's history. Therefore they must necessarily be constantly monitored with a correct follow-up and the decisions to be made to avoid unnecessary therapy when they have a poor outcome.